Meningkatkan Kapasitas Daya Tampung Drainase dengan Penggunaan Beton U-ditch pada Daerah Banjir Sidokare Dan Kawasan Kumuh Lemahputro Kota Sidoarjo - Renggar Ma'aris; Edy Gardjito; Yosef Cahyo Setianto Poernomo; Ashabul Yamin; Fitry Rahmawaty (Kadiri University, 2021)
The slums in Sidoarjo city are caused by people who ignore the cleanliness of the environment. The number of people who dispose of waste, household waste, or production waste in the channel causes the reduced function of drainage channels. This study aims to determine the capacity of existing channels in the flood area of Sidokare and Lemahputro slum, Sidoarjo. The method used uses a quantitative descriptive method—hydrological data obtained from rainfall recording stations for ten years. The data was then analyzed using rational methods to calculate the discharge of flood plans when resetting the 10-yearly. The hydrology and hydraulic analysis calculation results obtained plan discharge (Qr) of 0.092 m3/s and existing discharge (Qs) of 0.032 m3/s. These results showed the existing channel condition could not accommodate the discharge of rainwater runoff, so there needs to be redimence of the channel. From the analysis of the dimensions of drainage channels conducted, obtained a new channel in the form of Box U-Ditch with a channel depth (h) 0.50 width under the channel (b) 0.40 m, with channel discharge plan that 0.128 m3/s can accommodate.